2007
DOI: 10.1002/nvsm.334
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and forms of corporate giving behaviour: insights from Australia

Abstract: Although corporate support for many nonprofit organisations (NPOs) represents only a relatively small component of their overall income its importance is growing. As a consequence, the need to understand corporate giving behaviour in a way that supports the development of strategically targeted and successful marketing campaigns is of growing importance to marketing managers in many NPOs around the globe. This paper presents the findings of a study into the 'why' and 'how' of corporate giving behaviour in Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…This evidence builds on, but also departs from, the literature on HEIs as centres of calculation, seeking to know and control 'distant others' (Latour, 1987;Driver, 1992;Lambert and Lester, 2004;Jöns, 2009). Arguably, by contributing to knowledge produced by institutions located in the affluent regions, donors who were based -or had family origins -in the South reinforced the elitist position of leading Northern HEIs and perpetuated geographical and social inequalities (Salamon, 1987;Noble et al, 2008;Hopkins, 2011). However, our analysis has indicated that influential networks of transnational alumni were also active in shaping the priorities and research agendas of these same institutions, facilitating initiatives which ostensibly benefited individuals located in the South, and permitted the circulation of new knowledge beyond networks of elite HEIs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This evidence builds on, but also departs from, the literature on HEIs as centres of calculation, seeking to know and control 'distant others' (Latour, 1987;Driver, 1992;Lambert and Lester, 2004;Jöns, 2009). Arguably, by contributing to knowledge produced by institutions located in the affluent regions, donors who were based -or had family origins -in the South reinforced the elitist position of leading Northern HEIs and perpetuated geographical and social inequalities (Salamon, 1987;Noble et al, 2008;Hopkins, 2011). However, our analysis has indicated that influential networks of transnational alumni were also active in shaping the priorities and research agendas of these same institutions, facilitating initiatives which ostensibly benefited individuals located in the South, and permitted the circulation of new knowledge beyond networks of elite HEIs.…”
Section: Discussionmentioning
confidence: 85%
“…We found evidence of needs-based provision across a number of Although the gifts were presented as supporting students in 'need', this type of provision was frequently combined with an HEI's imperative to continue to operate at an elite level by seeking out the best 'talent'. As such, the presentation of these donations by HEIs raises questions about the underlying motivations of some universities in promoting equality of access (Noble et al, 2008). Moreover, the emphasis in the above examples on supporting a specific social group within a selected area, led to what Salamon has described as 'philanthropic particularism ' (1987: 39).…”
Section: (Iii) Facilitating Equality Of Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey conducted in 2001 has shown that one out of every five Australian shareholders value contributing to society above profit making (Ahmad et al, 2009). Noble et al (2008) find strategic, profit maximisation or political motives rather than altruistic or managerial utility motives for corporate philanthropy by Australian firms. Noble et al (2008) have provided useful insight into the broad decision-making structure to be found in Australian firms and have found that the donating decisions after the tsunami would, in general, have been made by a committee, with the effect that agency problems would have been ameliorated.…”
Section: Theoretical Framework 21 Corporate Philanthropymentioning
confidence: 82%
“…The events following this tsunami present a unique opportunity to examine the reporting of philanthropy by Australian corporations, as there was both extensive media coverage of contributing activity and well-publicised pressure on all corporations to reveal their contributions to their shareholders. Whereas corporate giving behaviour and motives have been extensively studied (Adams and Hardwick, 1998;Seifert et al, 2003Seifert et al, , 2004Campbell and Slack, 2006;Noble et al, 2008;Zhang et al, 2010), there is only a small body of literature about patterns of disclosure of corporate philanthropy by Australian firms. Jones (2005) carried out some of the first research in this field without access to data about donation size, while Ahmad et al (2009) look at disclosures to examine corporate philanthropy practices in Australia.…”
Section: Introductionmentioning
confidence: 99%